6 - Access to Drugs at Risk: Securing Access to Medicines for Least Developed Countries - Jurua, Maria (Africa Development, 2017)
Is access to medicines at risk despite the Doha Declaration? What are the alternative mechanisms that should be instituted to guarantee continued access to life saving drugs for many in the least developed countries (LDCs)? The Doha Declaration affirmed that patent rules should be interpreted and implemented to protect public health. Since Doha, access to drugs has dramatically increased to reach more than five billion people in developing countries. The Doha declaration also gave WTO members that are among the least-developed countries, an extended transition period, until 1 January 2016, with regard to pharmaceutical patents and test data protection for pharmaceutical products. The transition period extension in favour of least developed countries is to allow additional access to generic medicines. Post the transition period, efforts are needed to protect what has been achieved. This is necessary because of the stifled research and development for new drugs on neglected tropical diseases and the current trend of the abuse of intellectual property enforcement measures provided for in the Agreement on Trade-related Aspects of Intellectual Property Rights (TRIPs). Finding the right balance between health, trade and Intellectual Property policies to sustain innovation and ensure widespread access to life-saving technologies is one of the primary public policy challenges of our time.